Preventive measures in harmful crimes to public health - داوود, صباح سامي; أكبر, كولجين علي (Journal of Legal Sciences, 2019)
The prevention of crime is important in the field of public health the side of preventive him an important role as the side of therapeutic role ,the preventive measures in crimes harmful to public health have an important role in addition to the punitive methods has been identified legislator Iraqi a set of preventive measures to fight crime harmful to public health preventive measures to prevent the transmission of in fectious diseases as well as the interest in education, healthcare, environment ,health sound to maintain public health.We are in turn ,we study the preventive measures in crimes harmful to public health and the importance of its role in the prevention of crime prevention and, we explained the position of each of the Iraqi  legislation and international conventions and extent of interest approach preventive, and we department the search in to two section the first to show the concept of preventive measures and ,the second section to show the role of preventive measures to protect the public health and, we followed in the search the curriculum analytical descriptive.